2014
DOI: 10.1111/epi.12763
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy prevalence and socioeconomic deprivation in England

Abstract: SUMMARYObjective: Epilepsy is more prevalent in areas of greater socioeconomic deprivation; however, the factors that comprise this deprivation are not understood. We aimed to investigate the association between epilepsy, individual elements of deprivation, and geographic region in order to identify modifiable elements. Methods: Epilepsy prevalence was calculated via retrospective analysis of data recorded by general practitioners via the Quality and Outcomes Framework. The Index of Multiple Deprivation scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The possibility that early disadvantage contributed to smaller ICV in Generalized-CI cannot be ruled out. Population-based research has demonstrated higher rates of epilepsy in disadvantaged populations, the disadvantage not due to social drift ( Magnusson and Zelano, 2019 , Pickrell et al, 2015 , Steer et al, 2014 ), and racial and SES factors have been shown to influence features of epilepsy presentation ( Allen et al, 2018 , Allen et al, 2019 ). As disadvantage is known to impact cognition, brain and behavior in the general population, it appears important to more seriously consider these factors in the neuropsychology of epilepsy ( Baxendale and Heaney, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that early disadvantage contributed to smaller ICV in Generalized-CI cannot be ruled out. Population-based research has demonstrated higher rates of epilepsy in disadvantaged populations, the disadvantage not due to social drift ( Magnusson and Zelano, 2019 , Pickrell et al, 2015 , Steer et al, 2014 ), and racial and SES factors have been shown to influence features of epilepsy presentation ( Allen et al, 2018 , Allen et al, 2019 ). As disadvantage is known to impact cognition, brain and behavior in the general population, it appears important to more seriously consider these factors in the neuropsychology of epilepsy ( Baxendale and Heaney, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, regional differences in the standard of epilepsy care have been noted in the UK [20, 21], and may relate to personal preferences of the GP, practice type, size, location and local formulary access to certain AEDs. There is also a known correlation between social deprivation and increased epilepsy prevalence [22]. Additional relevant factors may have been excluded from the propensity scoring owing to lack of information in CPRD data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The societal impact of epilepsy has been wellstudied and documented in both print and other traditional media. For example, Steer et al found a strong correlation between the prevalence of epilepsy and socioeconomic deprivation [2]. Despite these findings, patients' disease experiences in addition to their desired care from the healthcare system vary greatly [3].…”
Section: Introductionmentioning
confidence: 99%